Partisipasi Politik Penyandang Disabilitas di Kota Semarang Pada Pemilihan Walikota dan Wakil Walikota Semarang 2015 - Sandra Febriyani Nur Ramadhani; Wachid Abdulrahman; Fitriyah . (Journal of Politic and Government Studies, 2017)
On December 9, 2015, for the first time, the Government holds simultaneous region headelection in 264 regions, one of all is Semarang. The most important thing in the election ofMayor and Vice Mayor is participation from all local citizens who already have voting rightsincluding the voters with a disability.This research aims to know the forms and factors that influenced the politicalparticipation of person with disability in Semarang on the Mayor and Vice Mayor election ofSemarang in 2015. The method used in this research is a combination quantitative research andqualitative research method, with the techniques of data collection is questionnaires andinterviews. To determine the sample is used accidental sampling, and to determine the subject ofresearch is used purposive sampling. The result showed that there were some forms of politicalparticipation of person with disability are joining the campaign, supporting a particularcandidate and became a participatory supervisor. Meanwhile, the factors that affect the politicalparticipation of person with disability, including data entry, socialization, facilities andaccessibility.The recommendations that can be done by KPU Kota Semarang is doing socializationseparately, present an interpreter when socialization, and ensure the tools for disability on theballot. The recommendation can be done by the family of the person with disability is not hidingtheir family members with a disability. And the recommendation that can be done by LocalGovernment is improving the database of disability.Keywords: Political participation, Person with Disability, Mayor election